2020
DOI: 10.1093/nutrit/nuaa093
|View full text |Cite
|
Sign up to set email alerts
|

Energy expenditure during pregnancy: a systematic review

Abstract: Context Contrary to nutritional guidelines, accumulating evidence shows that pregnant women’s energy intakes remain stable throughout trimesters. Although pregnant women may eat below their needs or underreport their energy intakes, it is also relevant to question how energy requirements – estimated through measurements of energy expenditure (EE) – change throughout pregnancy. Objective This review examined prospective studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 65 publications
(221 reference statements)
0
12
0
Order By: Relevance
“…Correlation does not imply causation, and so – although all studies on energy expenditure during pregnancy show that maternal energy turnover peaks around the time of birth (Savard et al ., 2021 ) – it is possible that maternal metabolism has adapted to the duration of gestation rather than vice versa . The fact that most women in energetically non‐stressed populations gain weight and continue to increase adipose tissue storage particularly during late pregnancy contradicts the notion that maternal energy resources are fully depleted near the time of birth.…”
Section: Alternative and Complementary Views To The Obstetrical Dilemma Hypothesismentioning
confidence: 99%
“…Correlation does not imply causation, and so – although all studies on energy expenditure during pregnancy show that maternal energy turnover peaks around the time of birth (Savard et al ., 2021 ) – it is possible that maternal metabolism has adapted to the duration of gestation rather than vice versa . The fact that most women in energetically non‐stressed populations gain weight and continue to increase adipose tissue storage particularly during late pregnancy contradicts the notion that maternal energy resources are fully depleted near the time of birth.…”
Section: Alternative and Complementary Views To The Obstetrical Dilemma Hypothesismentioning
confidence: 99%
“…Body composition changes dynamically during energy consumption. A reasonable BMR is significant for recommending dietary energy consumption during pregnancy ( 76 ). Pregnancy is a unique and complex physiological process.…”
Section: Discussionmentioning
confidence: 99%
“…It remains controversial regarding the ideal method to monitor/manage total energy during pregnancy. [ 9 , 10 ] The most widely used method is based on pre-pregnant body mass index (BMI), although this method often leads to an overestimation of the caloric needs in obesity/overweight women. [ 9 ] An excess of caloric intake leads to hyperglycemia with increased CO 2 , free fatty acid, and excess GWG.…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 ] REE shows a significant correlation with energy intake (EI). [ 10 , 19 ] Weight and body fat are important factors contributing to variability of REE during pregnancy and are correlated to cumulative REE in pregnancy. Recently, studies have found that changes of REE reflect increase in calorie needs and weight gain.…”
Section: Introductionmentioning
confidence: 99%